The neural development of the biological motion processing system does not rely on early visual input. (October 2015) - Bottari, Davide; Troje, Nikolaus F.; Ley, Pia; Hense, Marlene; Kekunnaya, Ramesh; Röder, Brigitte
Abstract: Naturally occurring sensory deprivation in humans provides a unique opportunity to identify sensitive phases for the development of neuro-cognitive functions. Patients who had experienced a transient period of congenital visual deprivation due to bilateral dense cataracts (congenital cataract, cc) have shown, after visual re-afferentation, deficits in a number of higher visual functions including global motion and face processing. By contrast, biological motion (BM) perception seemed to be spared. The present study investigated the neural correlates of BM processing in a sample of 12 congenital cataract-reversal individuals who had underwent visual restoration surgery at the age of a few months up to several years. The individual threshold for extracting BM from noise was assessed in a behavioral task while event-related potentials (ERPs) were recorded in response to point-light displays of a walking man and of a scrambled version of the same stimuli. The threshold of the cc group at detecting BM did not differ from that of a group of matched controls (mc). In both groups, the N1 was modulated by BM. These largely unimpaired neural responses to BM stimuli together with a lack of behavioral group differences suggest that, in contrast to the neural systems for faces the neural systems for BM processing specialize independent of early visual input.